Results of the summative stage of research and experimental work in detection schoolchildren's civic culture full development level - Volodymyr Kostiv (Vasyl Stefanyk Precarpathian National University, 2018)
The article presents the results of research and experimental work in civic culture full development level of 7th-11th grade pupils of a comprehensive school. It characterizes organization and methods of the research. The article gives results of senior pupils' civic culture orientation full development, their separate integrative civic qualities and general levels of civic culture full development levels of the tested schoolchildren. It characterizes representatives of each of the extracted typological groups (with high, medium, low and the lowest levels of full development of separate integrative qualities of the civic culture). It summarizes by giving a general profile of the personality's civic culture of one of the pupils and outlines perspectives for correcting the sphere of his further civic behavior. Key words: civic culture of a personality, organization of research and experimental work, research methods, results of full development of the integral civic culture qualities of 7th-11th grade pupils, characteristics of typological groups in accordance to general level of schoolchildren's integrative civic qualities full development, characteristics of a personality's civic culture profile of one of the schoolchildren, perspectives for correcting civic culture behavior.